1995
DOI: 10.1111/j.1559-1816.1995.tb01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Categories of Experience and Mental Health in a Sample of Managers

Abstract: This study of 28 managers investigated the importance for mental health of Jahoda's (1982) five categories of experience, measured for both work and leisure. Each of the categories of experience of time structure, social contact, collective purpose, status, and activity correlated with at least one measure of mental health. Multiple regression analysis showed that collective purpose and status, in both work and leisure, had moderate to large β coefficients, indicative of their potential influence, for a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Jahoda's (1981Jahoda's ( , 1982Jahoda's ( , 1997 propositions have received empirical support in several cross-sectional studies, which demonstrated that employed persons have more access to the latent functions than unemployed persons and persons who are out of the labour force (Creed & Reynolds, 2001;Waters & Moore, 2002). The latent functions were also shown to be positively correlated with mental health (Creed & Macintyre, 2001;Haworth & Paterson, 1995;Wanberg, Griffiths, & Gavin, 1997;Waters & Moore, 2002), and recently conducted longitudinal studies support the assumption that these correlations reflect an underlying causal effect of the latent functions on mental health (Selenko, Batinic, & Paul, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…Jahoda's (1981Jahoda's ( , 1982Jahoda's ( , 1997 propositions have received empirical support in several cross-sectional studies, which demonstrated that employed persons have more access to the latent functions than unemployed persons and persons who are out of the labour force (Creed & Reynolds, 2001;Waters & Moore, 2002). The latent functions were also shown to be positively correlated with mental health (Creed & Macintyre, 2001;Haworth & Paterson, 1995;Wanberg, Griffiths, & Gavin, 1997;Waters & Moore, 2002), and recently conducted longitudinal studies support the assumption that these correlations reflect an underlying causal effect of the latent functions on mental health (Selenko, Batinic, & Paul, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…Downloaded by [Bibliothèques de l'Université de Montréal] at 12:01 03 December 2014 rent well-being of the individual, but which, nevertheless, can produce high enjoyment, which can also be associated with a range of other positive subjective states and better psychological well-being (Csikszentmihalyi andCsikszentmihalyi, 1988, Clarke &Haworth, 1993).…”
Section: Winter-1994mentioning
confidence: 97%
“…Another study on the importance of ACE in work and leisure for mental health was undertaken on a sample of managers by Haworth & Paterson (1993). This showed that all of Jahoda's five categories of experience in both work and leisure correlated with at least one of a range of measures of psychological well-being.…”
Section: I0mentioning
confidence: 99%
“…Until recently, research has largely examined the two theories independently and support has been found for both (e.g., Creed & Machin, 2002;Creed & Macintyre, 2001;Haworth & Paterson, 1995;Whelan, 1992). From studies that have integrated the theories, it appears that the manifest benefit, typically operationalised as financial strain or economic deprivation, is a better predictor than latent deprivation of well-being in unemployed samples (Brief et al, 1995;Creed & Macintyre, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental effects of unemployment on the psychological wellbeing of the unemployed have been firmly established in the literature (see Feather, 1990;Murphy & Athanasou, 1999;Winefield, 1995 for reviews). Theories of economic and latent deprivation, predominantly those of Jahoda (1982) and Fryer (1986), have been used by many researchers to explain the deterioration in well-being typically experienced by the unemployed (Brief, Konovsky, Goodwin, & Link, 1995;Creed & Evans, 2002;Creed & Macintyre, 2001;Creed, Muller, & Machin, 2001;Haworth & Paterson, 1995). Jahoda (1982) proposed that employment provides access to five important categories of experience, including time structure, activity, social contact, collective purpose, and status.…”
Section: Introductionmentioning
confidence: 99%